Optimizing site selection for solar PV panel using AHP in marginal Kansas - Tasnim, Mobashsira (Kansas State University, 2024)
Energy demand in the United States is expected to increase by 15% between 2020 and 2050. With increasing demand our reliance on non-renewable energy is rapidly decreasing. While the adoption of renewable energy has significantly decreased CO2 emissions, a major limitation still lies in the deployment of these energy structures. Solar energy has become one of the most reliable non-renewable energy resources for its green and clean attributes. However, the installation of solar photovoltaic panels has the potential to compete with agricultural land cover due to their vast land requirement, approximately 4-5 acres of land for 1MW capacity. The state of Kansas is one of the top 10 sunniest states of the United States, however, this sunflower state is lagging behind in terms of solar-based energy generation. My thesis focuses on identifying suitable sites for solar photovoltaic plants in marginal lands that are unproductive, underutilized, and unfavorable for agricultural production. Firstly, the thesis adopts an overlay approach to identify marginal lands in Kansas. Along with quantifying and identifying marginal lands, the thesis also attempts to validate the quantified marginal lands in Kansas. According to my result, the state of Kansas covers approximately 0.4736 million hectares or 1,170,185.54 acres of marginal lands. Secondly, by utilizing secondary data and experts’ opinions through a Qualtrics survey, my research aims at identifying suitable SPV sites in Kansas. This thesis adopted a GIS-based multi-criteria approach to rank the marginal land cover in Kansas from most to least suitable for SPV deployment. The overall SPV suitability map shows that only 770 km²/ 0.077 million hectares of suitable marginal lands carries the highest potential for developing SPV power plants in Kansas. However, approximately 90% of the suitable marginal lands are very high to moderately suitable for SPV deployment, which indicates a high potential for future SPV projects in Kansas. Finally, by identifying the most suitable sites in marginal lands, my research broadly aims at promoting SPVs in Kansas while avoiding land covers that are utilized for food production.
Keywords: Solar photovoltaics (SPV); Geographic information system (GIS); Multicriteria decision analysis; Marginal lands